Double Trouble in Systemic Sclerosis: Complete Heart Block and Systolic Dysfunction - Akshyaya Pradhan; Sameer Ganpat Vankar; Pravesh Vishwakarma; Rishi Sethi (Journal of Clinical and Diagnostic Research, 2018)
A 26-year-old female, a known case of diffuse systemic sclerosis present with multiple episodes of syncope and progressive dyspnoea over six months. Her electrocardiogram revealed complete heart block and left ventricular systolic dysfunction with Ejection fraction of 42%. She underwent single chamber permanent pacemaker implantation and systolic dysfunction was managed medically. This case exemplifies a unique case of diffuse systemic sclerosis presenting with two rare primary cardiac manifestations namely complete heart block and systolic dysfunction, which occurred simultaneously.